Analisis Alih Kode, Campur Kode, Interferensi, Dan Integrasi Dalam Video Tiktok Akun “Sabreen” - Cristin Ameria; Lusia Gita Vanesa; Mika Charolin; Mesya Fadilla; Intan Valiza; Nadine Yusuf (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze linguistic phenomena, including code-switching, code-mixing, interference, and language integration, in TikTok videos from the account @Sabreensdiary. This research employs a descriptive qualitative approach with data collection techniques using observation and note-taking methods. The primary data source is a TikTok video uploaded on December 26, 2025, supported by captions and user comments. The findings reveal that code-mixing is the most dominant phenomenon, particularly in the form of English words and phrases inserted into Indonesian (outer code-mixing). Code-switching is also identified in several forms, including metaphorical, intrasentential, and extrasentential switching. Meanwhile, interference is not significantly found, as there are no deviations from Indonesian grammatical rules. Language integration is evident in commonly used words such as vibes, sunset, and headphone. The factors influencing these phenomena include bilingualism, language contact through digital media, social prestige and identity, communicative efficiency and expressiveness, as well as globalization and popular culture. These phenomena have both positive and negative impacts. Positively, they enhance linguistic creativity, strengthen social identity, and expand vocabulary. However, they may also lead to language shift, communication gaps, and the weakening of standard Indonesian usage.